2017
DOI: 10.1136/oemed-2016-104107
|View full text |Cite
|
Sign up to set email alerts
|

Biomass smoke exposure as an occupational risk: cross-sectional study of respiratory health of women working as street cooks in Nigeria

Abstract: This study provides evidence of adverse respiratory effects among street cooks using biomass fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
2
17
0
1
Order By: Relevance
“…Similar results was demonstrated by van Rooy et al among food flavouring workers in Europe [ 46 ]. Reduced spirometric indices among street cooks has also been shown in an earlier study in the area [ 36 ]. However, this comparison must be interpreted with caution, as only female respondents were assessed.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar results was demonstrated by van Rooy et al among food flavouring workers in Europe [ 46 ]. Reduced spirometric indices among street cooks has also been shown in an earlier study in the area [ 36 ]. However, this comparison must be interpreted with caution, as only female respondents were assessed.…”
Section: Discussionsupporting
confidence: 70%
“…This may be due to the irritant effect of inhaled caustic fumes on the workers, poor ventilation in the production area and the lack of effective personal protective equipment. Awopeju et al have shown that fume inhalation caused significantly higher odds of respiratory symptoms among a subset of female street cooks in Nigeria [ 36 ]. Particulate Matter analysis of the fumes, however, revealed benzene was the major culprit.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the author observed that symptoms compromising the respiratory system occurred more frequently amongst these women compared with the control group. The respiratory symptoms observed in the women were a cough and phlegm with a higher incidence of airway obstruction [35].…”
Section: Literature Reviewmentioning
confidence: 98%
“…Furthermore, Owili et al [44] observed that continued use of charcoal and biomass was linked with a high risk of mortality in children under five years of age in Sub-Saharan Africa. Awopeju et al [35] in Nigeria provided evidence of the adverse effects that biomass fuels had on the respiratory systems of women who cooked on the streets using biomass fuels. The authors found that there were higher chances of respiratory symptoms amongst these women compared with a control group.…”
Section: Socioeconomic Dynamics and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation